Exploring the crowding-satisfaction relationship of skiers: the role of social behavior and experiences. Issue 8 (21st November 2020) - Pikkemaat, Birgit; Bichler, Bernhard Fabian; Peters, Mike
ABSTRACT: Previous research has shown that crowding represents an essential factor in driving overtourism and highlighted the negative effects of crowding. However, there is limited knowledge of how crowding affects skiers' experiences and what variables drive the crowding-satisfaction relationship. Our findings show that individual skill levels and the behavior of other skiers moderate this relationship. These findings are supported by a set of interviews, which focus on skiers' crowding experiences. Our contribution provides a refined understanding of crowding in the ski context through highlighting the importance of tourist-to-tourist encounters to better understand the effects of crowding and suggests visitor management techniques.